Implementasi Nilai-Nilai Karisma Kasih melalui Desain Pengalaman Belajar (DPB) Ora et Labora untuk Meningkatkan Kualitas Sikap dan Prestasi Belajar Siswa SMA Swasta RK Bintang Timur Pematangsiantar - San Hendrin; Gregorius Daru Wijoyoko (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This classroom action research aims to improve students’ attitudes and learning achievement through the implementation of Karisma Kasih values within the Ora et Labora Learning Experience Design (DPB) at RK Bintang Timur Catholic Senior High School, Pematangsiantar. The Ora et Labora approach integrates spiritual and academic dimensions through reflective and collaborative learning experiences. The study employed the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 32 tenth-grade students enrolled in Catholic Religious Education. Data were collected through observation, attitude questionnaires, and learning achievement tests, and were analyzed using qualitative and quantitative descriptive methods. The results revealed significant improvements in faith-based attitudes, collaboration, and social responsibility, along with an increase in students’ average academic score from 73.5 in the first cycle to 84.2 in the second cycle. These findings indicate that integrating Karisma Kasih values through the Ora et Labora approach fosters meaningful learning, strengthens Christian character formation, and enhances students’ academic performance. This model is recommended as a contextual pedagogical strategy for promoting holistic Catholic education.